Analisis Pembuktian Dan Pertimbangan Hakim Dalam Putusan Yang Menyatakan Bebas Dari Segala Dakwaan Dalam Perkara Korupsi - Nur Rohadi (Sebelas Maret University, 2017)
This research aims to: 1) analyzes the process of proof in the criminal offence of corruption is already in compliance with the principles of the Law The Crime Of Corruption and the KUHAP. 2) analyzes the basic consideration of judges in meting out the verdict declaring the accused free of all claims in the case already in accordance with article 183 jo Article 191 paragraph (1) of the KUHAP. Based on the results of research and discussion, researchers conclude that: the process of proof in the criminal acts of corruption in the ruling of the No.78/Pid. Sus/2011/PN-Tipikor-Smg is based on the instruments of evidence submitted in the trial courts. The implications of information experts on corruption trial loan BPR Djoko Tingkir Sragen significantly to prove the charges by the public prosecutor, as evidenced by the description used by experts who break the juridical construction the public prosecutor so that the prosecution had not met primair and prosecuted with charges of subsidair. Keywords: Proving The Crime of Corruption, Non Ruling